Sperm DNA fragmentation index of alpaca (Vicugna pacos) using the sperm chromatin dispersion test - Huanca, Nancy (2020)
The aim of this study was to analyse the DNA fragmentation in alpaca spermatozoa recovered from the vas deferens deviation (VDD), as well as those collected by electroejaculation (EE) and by post-copula (PC). The sperm was collected from three males per method and three times per animal. Volume, motility, concentration, vitality, functionality of the spermatic membrane and sperm DNA fragmentation index were evaluated. Microscopic variables were evaluated with the Integrated Semen Analysis System - ISAS®; the sperm DNA fragmentation index (DFI) was determined by the chromatin dispersion method (VDD). The DFI data was analysed using a completely randomized block design. An DFI of 36.44 ± 22.50% was found in the VDD method and 13.65 ± 18.98% and 8.42 ± 10.28% for sperm collected by EE and PC, the latter two being superior (p<0.05) to the VDD method. A lower percentage of sperm DNA fragmentation was found in semen collected by post-copulation and electroejaculation.